2021
DOI: 10.15694/mep.2021.000004.1
|View full text |Cite
|
Sign up to set email alerts
|

Online Test Application during COVID-19 Pandemic: Academic Impact on Medical Students of the biggest School of Medicine in Mexico

Abstract: Introduction: Online assessment is an educational alternative in this health emergency generated by COVID-19. To meet the educational demands of the School of Medicine of the UNAM, we implemented the evaluation of their subjects of the Medical Bachelor online, avoiding the delay of the school career of their students. Methods: A quantitative analysis was conducted to evaluate the academic performance of students enrolled in the first and second year of the degree of Medical Bachelor, being the school years wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Six out of 11 studies showed differences in outcome of before and during COVID-19 pandemic 2 , 24 , 31 , 35 , 36 , 39 and five other studies with no difference in outcome. 28 , 32 , 33 , 37 , 40 It means that more studies reported the influence of COVID-19 pandemic situation to academic performance.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…Six out of 11 studies showed differences in outcome of before and during COVID-19 pandemic 2 , 24 , 31 , 35 , 36 , 39 and five other studies with no difference in outcome. 28 , 32 , 33 , 37 , 40 It means that more studies reported the influence of COVID-19 pandemic situation to academic performance.…”
Section: Resultsmentioning
confidence: 92%
“… To analyze the sleep quality among medical students in Al Qunfudhah College of medicine and its effects on their academic performance during COVID-19 pandemic Single Medical School Undergraduate 198 Sleep quality GPA Sleep quality among most of them and negatively affected their academic performance. Fernandez-Altuna et al, 31 2021, Mexico, Cohort. To estimate the statistical difference between the face-to-face assessments in 2019 and the assessments conducted online in 2020 in response to the health emergency by COVID-19, of students enrolled in the first and second year of the UNAM School of Medicine Single Medical School Undergraduate 4737 Assessment in 2019 and 2020 Regular exams score in 16 subjects There is a significant difference obtained in the academic performance of the two school years (2019 face-to-face VS 2020 online) where students in 2020 have a higher graduation rate than students in 2019 Y.H.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations